Citizen Journalism and its Rise to Prominence in the Context of the Nigerian Contemporary Society - Inobemhe, Kelvin; Garba, Suleiman (Bodhi: An Interdisciplinary Journal, 2025)
Over the past few decades, Nigeria has seen a major changein its media landscape with the emergence of citizen journalism. The issues accompanying the growing adoption of the concept continue to generate concerns in the media landscape and the larger society. Therefore, this study explored the role, development, and impact of citizen journalism in Nigerian society. At its heart, the problem is the difficulty for mainstream media in engaging with urgent problems and the erosion of trust between the public and traditional news outlets. Information can now be shared by ordinary citizens on social media, which has led to the rise of citizen journalism. This study, therefore, applied gatekeeping theories and the concept of the public sphere to provide insights into the manner in which citizen journalism has subverted mainstream media narratives. Employing a systematic literature review methodology, the researchers relied on secondary sources (e.g., journal articles and reports) and examined the factors that gave rise to this new journalism. Findings showed that citizen journalism can facilitate the transmission of news but also creates problems due to misinformation and ethical concerns. In the end, the researchers showed that citizen journalism empowered many Nigerians to be heard, particularly in political events and crises, although it presented unique challenges. The recommendations focused on the need for more media literacy campaigns and stronger regulatory frameworks to combat the threats of misinformation.